MIDD0301 – A first‐in‐class anti‐inflammatory asthma drug targets GABAA receptors without causing systemic immune suppression. Issue 1 (21st February 2019) - Zahn, Nicolas M.; Huber, Alec T.; Mikulsky, Brandon N.; Stepanski, Mae E.; Kehoe, Alexander S.; Li, Guanguan; Schussman, Melissa; Rashid Roni, Mohammed S.; Kodali, Revathi; Cook, James M.; Stafford, Douglas C.; Steeber, Douglas A.; et al.
Abstract: We report a 28‐day repeat dose immunotoxicity evaluation of investigational drug MIDD0301, a novel oral asthma drug candidate that targets gamma amino butyric acid type A receptors (GABAA R) in the lung. The study design employed oral administration of mice twice daily throughout the study period with 100 mg/kg MIDD0301 mixed in peanut butter. Compound dosing did not reveal signs of general toxicity as determined by animal weight, organ weight or haematology. Peanut butter plus test drug (in addition to ad libitum standard rodent chow) did not affect weight gain in the adult mice, in contrast to weight loss in 5 mg/kg prednisone‐treated mice. Spleen and thymus weights were unchanged in MIDD0301‐treated mice, but prednisone significantly reduced the weight of those organs over the 28‐day dosing. Similarly, no differences in spleen or thymus histology were observed following MIDD0301 treatment, but prednisone treatment induced morphological changes in the spleen. The number of small intestine Peyer's patches was not affected by MIDD0301 treatment, an important factor for orally administered drugs. Circulating lymphocyte, monocyte and granulocyte numbers were unchanged in the MIDD0301‐treated animals, whereas differential lymphocyte numbers were reduced in prednisone‐treated animals. MIDD0301 treatment did not alter IgG antibody responses to dinitrophenyl following dinitrophenyl‐keyhole limpet haemocyanin immunization, indicating that systemic humoral immune function was not affected. Taken together, these studies show that repeated daily administration of MIDD0301 is safe and not associated with adverse immunotoxicological effects in mice.